Dibromoindium(iii) cations as a π-Lewis acid: characterization of [IPr·InBr2][SbF6] and its catalytic activity towards alkynes and alkenes12. Issue 34 (31st March 2015) - Michelet, Bastien; Colard-Itté, Jean-Rémy; Thiery, Guillaume; Guillot, Régis; Bour, Christophe; Gandon, Vincent
Abstract : [IPr·InBr2 ][SbF6 ] (2 ) (IPr = 1, 3-bis(2, 6-diisopropylphenyl)imidazol-2-ylidene) has been synthesized, characterized in the solid state, and used as catalyst. Abstract : [IPr·InBr2 ][SbF6 ] (2 ) (IPr = 1, 3-bis(2, 6-diisopropylphenyl)imidazol-2-ylidene) has been synthesized and characterized in the solid state. This complex proved to be a very active catalyst for hydroarylations, transfer hydrogenations, and cycloisomerizations.